Late Cenozoic erosion in the SW Barents Sea, and its influence on salt movement - Martinsen, Birgitta Saue (UiT Norges arktiske universitet, 2019)
The late Cenozoic evolution of the southwestern Barents Sea shelf includes periods of uplift, erosion and glaciations. This part of the stratigraphy has been studied using 2D and 3D seismic data, with emphasis on the interplay between uplift, erosion and glaciations and salt movement. The study area comprises the Svalis, Samson and Norvarg domes and the Nordkapp Basin, where halokinesis has been a major influence on the tectonostratigraphic evolution. The study includes systemization and categorization of the timing of salt activity relative to the erosion of the shelf, in the Nordkapp Basin, and on the Svalis, Samson and Norvarg domes. Very late to almost recent salt movement has occurred within some of the diapirs in the Nordkapp Basin and the Svalis Dome, evidenced by uplift of the Upper Regional Unconformity (URU) surface and the seafloor above the salt. Furthermore, the study reveals significant local variations in salt movement of the diapirs in the Nordkapp Basin, with a trend of more late salt movement towards the northeast. This is possibly attributed to a larger original salt thickness in this part of the basin compared to in the southwest. A mini-basin filled with glacigenic sediments is found adjacent to the Svalis Dome, and this is assumed to be a result of a combination of deeper glacial erosion of less resistant strata on the Loppa High, and less exposure to erosion due to the continuous salt rise and elevation of the adjacent dome. The Norvarg and Samson domes are not found to be influenced by late Cenozoic salt movement, which is attributed to factors such as original salt thickness, overburden strength and early Cenozoic erosion. Spatial variations in lithology due to salt-related doming and faulting is assumed to have influenced both the pre-glacial and later glacial erosion of the Norvarg Dome during the Cenozoic. Overall, the relationship between salt diapirism, erosion and glacial influence is found to be complex. The structural elements within the study area have experienced different ...